Analyzes The Effect Of Service Quality Factors Toward Consumer Loyalty To PT. Indosolo Motor Gemilang Surakarta - Kusumo, Baskoro; , Dra. Rina Trisnawati, M.Si, Ph.D, Ak, CA (2014)
This study aims to analyze the general impact of service quality on customer loyalty which consists of dimensions tangible, reliability, responsiveness, assurance, and empathy towards customer loyalty. Specific objectives of this study were: 1) to analyze the effect of tangible dimension, reliability, responsiveness, assurance, and empathy for customer loyalty in the PT. Indosolo Motor Gemilang Surakarta. 2) Analyze the most dominant factor among tangible, reliability, responsiveness, assurance, and empathy towards customer loyalty PT. Indosolo Motor Gemilang Surakarta, the sample used is the consideration of 60 people with 10 multiplied 6 because this study used five independent variables and the dependent variable. Based on consideration of the researcher, given the possibility of 60 respondents were unable to fill the questionnaire in full, the researchers spread as much as 150% of the questionnaire sample should (60 respondents) ie 90 respondents, the sampling technique using accidental sampling. Data analysis method used is multiple linear regression while the statistical test using the t test and F test and test-R2. The results of this study indicate tangible dimension of service quality, reliability, responsiveness, assurance, empathy jointly influence on customer loyalty. Partial all dimensions there are tangible dimension, reliability, responsiveness, assurance, and empathy also affect customer loyalty. Assurance variable is the variable most dominant compared to other variables